Enhancement of microstructural and magnetic properties of high spin Mn substituted nanocrystalline Ni–Mn–Cu–Zn ferrites - Abdul Ahad; A.K.M. Akther Hossain (Heliyon, 2024)
Mn-substituted Cu and Zn co-doped spinel-typed nano-crystalline ferrites having nominal composition Ni0.50-xMnxCu0.15Zn0·35Fe2O4 (x = 0.00–0.25 in 0.05 increments) have been prepared through the citric acid assisted sol-gel auto-combustion technique. From the XRD measurements, it was found that several intense peaks ensured the cubic spinel-based ferrite structure beyond the formation of any impurity peaks. The crystallite sizes varied from 20 to 28 nm for ash-burnt powders following the coalescence process that decreased the lattice defects and strain. With an increase in Mn concentration, the hopping length (LA) of the tetrahedral A-site increases, while the hopping length (LB) of the octahedral B-site decreases with enhanced lattice constant. The sintered samples' average grain sizes, as measured using the Field Emission Scanning Micrographs (FESEM), differed from around 1.40 to 5.30 μm. Incorporating Mn-ion accelerates grain growth and crystallite size with increased bulk density and reduced porosity due to heat treatment. For increasing sintering temperature along with Mn concentration, porosity drops from 42% to 3%, resulting in enhancing the magnetic induction of the prepared ferrites. The 25% Mn substituted composition displays the maximum initial permeability (μi′ = 315), which is ∼7 times larger than the pristine composition. Due to the reduction of Ni content, the relative quality factor rises but the magnetic loss tangent reduces. An increased trends of μi′ are accompanied by decreased resonant frequency, obeying Snoek's law. According to the experimental findings, the high spin Mn substitution in the composition causes the saturation magnetization to increase while the coercivity and Néel temperature drop with increasing grain size. Hence, the locally prepared low-cost Nano-crystalline Ni–Mn–Cu–Zn ferrites bearing excellent properties can be a good candidate for promising future applications in nanotechnology.